The Locus Coeruleus–Norepinephrine System Mediates Empathy for Pain through Selective Up-Regulation of P2X3 Receptor in Dorsal Root Ganglia in Rats - Lü, Yun-Fei; Yang, Yan; Li, Chun-Li; Wang, Yan; Li, Zhen; Chen, Jun (Frontiers in Neural Circuits, 2017)
Empathy for pain (vicariously felt pain), an ability to feel, recognize, understand and share the painful emotions of others, has been gradually accepted to be a common identity in both humans and rodents, however, the underlying neural and molecular mechanisms are largely unknown. Recently, we have developed a rat model of empathy for pain in which pain can be transferred from a cagemate demonstrator (CD) in pain to a naïve cagemate observer (CO) after 30 min dyadic priming social interaction. The naïve CO rats display both mechanical pain hypersensitivity (hyperalgesia) and enhanced spinal nociception. Chemical lesions of bilateral medial prefrontal cortex (mPFC) abolish the empathic pain response completely, suggesting existence of a top-down facilitation system in production of empathy for pain. However, the social transfer of pain was not observed in non-cagemate observer (NCO) after dyadic social interaction with a non-cagemate demonstrator (NCD) in pain. Here we showed that dyadic social interaction with a painful CD resulted in elevation of circulating norepinephrine (NE) and increased neuronal activity in the locus coeruleus (LC) in the CO rats. Meanwhile, CO rats also had over-expression of P2X3, but not TRPV1, in the dorsal root ganglia (DRG). Chemical lesion of the LC-NE neurons by systemic DSP-4 and pharmacological inhibition of central synaptic release of NE by clonidine completely abolished increase in circulating NE and P2X3 receptor expression, as well as the sympathetically-maintained development of empathic mechanical hyperalgesia. However, in the NCO rats, neither the LC-NE neuronal activity nor the P2X3 receptor expression was altered after dyadic social interaction with a painful NCD although the circulating corticosterone and NE were elevated. Finally, in the periphery, both P2X3 receptor and 1 adrenergic receptor were found to be involved in the development of empathic mechanical hyperalgesia. Taken together with our previous results, empathy for pain observed in the CO rats is likely to be mediated by activation of the top-down mPFC-LC/NE-sympathoadrenomedullary (SAM) system that further up-regulates P2X3 receptors in the periphery, however, social stress observed in the NCO rats is mediated by activation of both hypothalamic-pituitary-adrenocortical axis and SAM axis.